X-ray tomography analysis of bubbles and slugs in a fluidized bed with inter-particle force. (December 2021) - Ma, Jiliang; Liu, Daoyin; Chen, Xiaoping; Liang, Cai; van Ommen, J. Ruud
Highlights: X-ray tomography was used to detect bubbles and slugs in a cohesive bed. Inter-particle force increases the gas-holding capacity of emulsion phase. Bubbles rise slower than theoretical values due to the reduced particle flowability. The frequency and size of slugs both increase with inter-particle force. There exist three slugging patterns for the bed with strong inter-particle force. Abstract: Bubbles and slugs coexist in a fluidized bed with strong inter-particle forces. However, the effects bubbles and slugs impose over fluidizing stability, and chemical reaction efficiency are different. The present work distinguished bubbles and slugs with the aid of X-ray tomography, and the evolution of their properties with varying inter-particle force in a fluidized bed were studied. The results show that the gas-holding capacity of the emulsion phase improves as inter-particle forces initially increase. In this process, the bubble frequency decreases noticeably, and the bubble size slightly increases. Bubbles rise slower than theoretically predicted because inter-particle force reduces the particle flow. The frequency and the size of slugs increase with inter-particle forces. As forces initially increases, the slug size increases with measurement height. An opposite trend is observed when inter-particle forces continues to strengthen. Near the gas distributor, the slug rising velocity is independent of size. In contrast, large slugs have a higher velocity than small slugs near the bed surface. Finally, three slugging patterns are distinguished, and the influence they impose on particle flow is analyzed. Graphical abstract: Image, graphical abstract